MANAJEMEN PROGRAM REALITY COMPETITION SHOW DI TELEVISI - Susanti, Santi; Suryana, Asep; Nugraha, I Gusti Wayan Albar (Jurnal Common, 2020)
This study aims to reveal the management of television entertainment programs in the form of reality competition shows that succeed in attracting the attention of the audience through seven aspects, namely conflict, duration, preferences, consistency, energy, timings, and trends. The qualitative method with the case study approach is used to study people involved in the production of D'Academy and D’Star in Indosiar, namely the production team, performers and the audience. The results are D'Academy and D'Star fulfilled seven aspects of the success of a television entertainment program with almost similar treatment as a dangdut competition program. The production team also carried out the commodification of the two programs, in the form of content commodification and the commercialization of the audiences relating to the aspects of the success of television entertainment program on D'Academy and D'Star. which is almost the same for aspects of the success of a program and has only a few differences that are tailored to the carried innovations.